Impact of hyperthermic isolated limb perfusion on tumour oxygenation in soft tissue sarcoma - Jakob, Jens; Rège, Inez von; Weiß, Christel; Hohenberger, Peter (International journal of hyperthermia and thermal therapies, 2012)
Purpose: Hyperthermic isolated limb perfusion (ILP) with recombinant tumour necrosis factor alpha (TNF) and melphalan contributes to limb-saving treatment in patients with locally advanced extremity soft tissue sarcoma (STS). This study was conducted to evaluate the dynamic changes of tumour oxygenation and temperature during ILP and their effects on treatment response.Patients and methods: Tumour oxygenation (pO2) and tumour temperature were measured by intratumourally placed O2-sensitive catheter electrodes in 34 patients who underwent ILP for locally advanced or recurrent STS. Tumour response to ILP was assessed by the fraction of tumour necrosis in the resection specimen.Results: Mean tumour pO2 prior to application of TNF and melphalan was 36 mm Hg (range: 2-116 mm Hg) and dropped significantly to 13 mm Hg (range: 0-67 mm Hg, p = 0.03) during ILP. Mean tumour tissue temperature increased from 34.4°C (range 32.4-36.4) to 38.5°C (range 34.1-40.4, p = 0.0001). The mean fraction of necrosis in the resection specimen was 65% (range 5-99). Only the tumour tissue temperature at the onset of ILP correlated with the extent of tumour necrosis (p = 0.01).Conclusion: ILP with TNF and melphalan induces severe oxygen deprivation in soft tissue sarcoma. However, changes in tumour oxygenation did not correlate with treatment response.